The trigonometric identity `sin^4x - cos^4x = 2*sin^2x - 1` has to be proved.

Start from the left hand side.

`sin^4x - cos^4x`

Use the relation `x^2 - y^2 = (x - y)(x +y)`

= `(sin^2x - cos^2x)(sin^2x + cos^2x)`

Use the property `sin^2x + cos^2x = 1`

= `(sin^2x - cos^2x)`

= `sin^2x - (1 - sin^2x)`

= `sin^2x - 1 + sin^2x`

= `2*sin^2x - 1`

**This proves that **`sin^4x - cos^4x = 2*sin^2x - 1`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.